Influência do ferro na produção de massa, área foliar e índice de clorofila total na baby leaf rúcula - Gastaldi, Vitor (Universidade Federal de São Carlos, 2023)
The aim of this study was to evaluate the effect of the iron nutrient in a hydroponic system using arugula baby leaf (Astro variety) in two seasons, summer and winter, on the characteristics: leaf area, fresh mass of shoots and roots, dry mass of the aerial and root and total chlorophyll index. The experimental design of the study was in randomized blocks, with a factorial of four doses of iron (T1=1.8; T2= 3.6; T3 = 5.4; T4 = 7.2 g.1000L-1). The results presented in the summer season were adequate, mainly in the concentration of T3, which presented higher values ​​for fresh mass of shoots, roots, leaf area and dry mass. For the winter season, the results were positive, since the fresh mass of the aerial part and the root, the dry mass of the aerial part and the chlorophyll index of the large leaves were higher and for the dry mass of the root, mainly using the T4 concentration. Comparing the seasons, it was found that the effect of iron was more adequate in the summer, since all mass parameters were higher. Iron supplementation in both seasons can bring benefits to the plant, producer and possibly the consumer.
Influence of iron on mass production, leaf area and total chlorophyll content in baby leaf arugula
Keywords: Cor; Massa Fresca; Massa Seca; Biofortificação; Color; Fresh mass; Dry mass; Biofortification; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::FISIOLOGIA POS-COLHEITA